Clinical experience with the use of serous apposition - Mesa Figueras, Guillermo; Zagia, Miguel; Cassinelli, Daniel (Cirugía del Uruguay, 1971)
Clinical experience in three cases of serous apposition in different locations and under different conditions is described in this paper. The treatment was successful and was subject to through testing; consequently it is well worth being taken into account in general surgical practice.